2017
DOI: 10.1007/s40273-017-0531-3
|View full text |Cite
|
Sign up to set email alerts
|

Reporting and Analysis of Trial-Based Cost-Effectiveness Evaluations in Obstetrics and Gynaecology

Abstract: Background and ObjectivesThe aim was to systematically review whether the reporting and analysis of trial-based cost-effectiveness evaluations in the field of obstetrics and gynaecology comply with guidelines and recommendations, and whether this has improved over time.Data Sources and Selection CriteriaA literature search was performed in MEDLINE, the NHS Economic Evaluation Database (NHS EED) and the Health Technology Assessment (HTA) database to identify trial-based cost-effectiveness evaluations in obstetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 84 publications
(220 reference statements)
0
28
0
Order By: Relevance
“…Whereas previous studies 8,9 have focused on assessing the methodological quality of individual EEs in obstetric care using a checklist (e.g. CHEERS Statement), 18 no in‐depth analysis was performed of what makes adherence to guidelines difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas previous studies 8,9 have focused on assessing the methodological quality of individual EEs in obstetric care using a checklist (e.g. CHEERS Statement), 18 no in‐depth analysis was performed of what makes adherence to guidelines difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews of EE studies in gynaecology and obstetrics, reported problems with adherence to guidelines, 6,7 although improvement over time has been observed 8,9 . However, it was still concluded that improvement of the methodological quality of EEs within the field of obstetrics and gynaecology remained possible and desirable.…”
Section: Introductionmentioning
confidence: 99%
“…The more alike participants are within a cluster, which is quantified using the intraclass correlation coefficient (ICC), the less new information is provided by a participant belonging to that same cluster. Despite the fact that statistical methods for dealing with clustered data are available and their use in effectiveness studies is well established [ 8 , 15 17 ], these methods are hardly used in trial-based economic evaluations [ 5 , 18 ]. In addition, no clear recommendations on how to deal with clustered data are available in pharmacoeconomic guidelines [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 The number of cost-effectiveness evaluations published annually in obstetrics and gynaecology has increased since 2000, with the majority being conducted alongside a clinical trial. 2 …”
Section: Introductionmentioning
confidence: 99%